Chemical Profiling of Leaf Essential Oil of Lantana camara Linn. From North-East India. Issue 5 (2nd September 2020) - Sarma, Neelav; Begum, Twahira; Pandey, Sudin Kumar; Gogoi, Roktim; Munda, Sunita; Lal, Mohan
Abstract: Lantana camara Linn., a noxious weed found in most places of the world has many potential aspects and has been used as folk medicines to cure several diseases. It is reported to possess antimicrobial, antioxidant, antidiabetic, anti-inflammatory, antiurolithiatic, wound healing, antifertility and cytotoxic activities. The plant leaf essential oil in the present study was obtained by hydrodistillation method and further analyzed by Gas Chromatography/Mass Spectroscopy. Twenty-two compounds were detected owing to 88.97 % of the total essential oil percent. Major compounds identified in the L. camara leaf essential oil were β-caryophyllene (24.96 %) and δ-selinene (17.46 %), while compounds with intermediate concentration were β-copaene (09.55 %), bicylogermacrene (6.69 %), β-phellandrene (6.49 %) and δ-cadinene (4.95 %). Few of the other minor compounds such as 3-carene (2.74 %), limonene (2.48 %), α-copaene (1.88 %), β-germacrene (1.88 %) and geranyl formate (1.64 %) were also identified in considerable quantities. Among the total identified compounds, 12.79 % of monoterpenes, 0.98 % of alkylbenzene, 1.64 % of fatty alcohol esters and 73.56 % of sesquiterpenes were found in the leaf essential oil of L. camara . The present investigation revealed the chemical profiling of L. camara leaf essential oil from North East India for the very first time and also highlights their applications as well as a relative analysis of the essential oil composition.